FAILURE IN THE MANAGEMENT OF MANDIRI VILLAGE-OWNED ENTERPRISE (BUMDES) TANJUNG MEDAN VILLAGE, CERENTI DISTRICT, KUANTAN SINGINGI DISTRICT, 2019-2020 - Pebri, Lidia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Tanjung Medan Village has a BUMDes which operates in the field of selling goods and services. Tanjung Medan BUMDes was initially formed on December 18 2019. According to the mandate of PERDA Number 5 of 2019 concerning the establishment of BumDes, Kuansing Regency, article 16 explains that BumDes must at least develop and have a profit of at least 10 % and the last 2 years. However, in this village it is not running and does not fulfill these benefits. The aim of the research is to find out and analyze what factors influence the failure of BumDes Mandiri management in Tanjung Medan Village, Cerenti District, Kuantan Singingi Regency. This research uses the theory of Good Governance, which has been well known in Indonesia since the 1990s. This research method is descriptive research with a qualitative approach. The data sources used are primary and secondary data. The data collection technique used was through interviews and documentation. The research results show that the failure of the Mandiri Village-Owned Enterprises (BUMDES) in Tanjung Medan Village, Cerenti District, Kuantan Singingi Regency in 2019-2020 has not gone well, this is due to a lack of communication between the village government and BUMDes management. This is due to a lack of awareness of BUMDes management which has never received guidance from its directors or members from either the province, district or village government itself. This research concludes 2) The obstacles that occurred in Mandiri Village-Owned Enterprises (BUMDES), Tanjung Medan Village, Cerenti District, Kuantan Singingi Regency in 2019-2020, namely not implementing the principles of good governance due to a lack of understanding of both the BUMDes Director and its members and no efforts by the village government to This resulted in failure in running a business entity in the village. Keywords: Failure, Management, Village-Owned Enterprises (BUMDes)